P-022 Treating symptomatic intracranial atherosclerosis with the balloon expandable Pharos Vitesse neurovascular stent: initial experience. (16th November 2010) - Wakhloo, A; Patel, N; Thors, A; Duhamel, E; Morris, J; Ramzan, M; Moonis, M; Gounis, M
Abstract : Purpose: To describe our early experience with the balloon expandable Pharos Vitesse stent for symptomatic, high grade intracranial stenosis. Materials and methods: Our center has enrolled five patients to date in the VISSIT (Vitesse Intracranial Stent Study for Ischemic Therapy) Trial.1 This prospective, multicenter, randomized trial is designed to compare best medical therapy alone to best medical therapy plus stenting for symptomatic, high grade intracranial stenosis. In conformance with the study design, patients were treated for 70–80% stenosis (inclusion criterion 70–99%) of the intracranial internal carotid, middle cerebral or intradural vertebral arteries. The patients ranged from 49 to 76 years of age (mean 63). There were four men and one woman. All target lesions and vessels were of appropriate size for treatment using the Pharos Vitesse stent. All patients underwent neurological assessment, including evaluation of the modified Rankin Scale (mRS) and CT studies prior to diagnostic digital subtraction angiography (DSA). Four patients also underwent CT perfusion (CTP). After diagnostic DSA, three patients were randomized to the stenting arm of the trial. One patient who was randomized to the medical therapy arm failed medical therapy and underwent stenting after recurrent ischemic stroke in the territory of the stenotic vessel. After stenting, mRS and CTP were performed in all patients prior to discharge. Results: Stenting was technically successful in all cases. In three cases, there was no residual stenosis. In one case, heavily calcified, concentric atherosclerotic plaque resulted in residual stenosis of 30%. There were no procedural complications. One patient recovered from anesthesia with neurologic deficits localizable to the treated territory. These resolved completely and spontaneously within 24 h. No other periprocedural neurological adverse events were encountered. Two of three patients undergoing stenting had abnormal CTP findings in the territory distal to the stenotic lesion. In one, MTT was prolonged (>1.5× the contralateral side) in a large portion of the right middle cerebral artery (MCA) territory (90.8 cm 3 tissue volume). In another, MTT was prolonged in the right MCA/posterior communicating artery watershed territory (5.3 cm 3 tissue volume). All patients had normal CTP examinations at discharge. The 30 day mRS (median 1, range 0–6) were either stable or improved, compared with the mRS at presentation, in 3/4 patients. The fourth patient died >30 days after randomization due to complications of a previously unknown metastatic prostate cancer. The patient that was randomized to medical therapy awaits 30 day assessment. One patient returned 5 months after stenting with symptoms of transient ischemic attack in the treated territory. Although no residual stenosis was present initially, a flow restricting restenosis was identified on DSA. This was treated successfully using balloon angioplasty. Conclusion: In our early experience, treatment of symptomatic, high grade intracranial stenosis with the Pharos Vitesse stent is a safe procedure that has resulted in no permanent procedure related complications. Following stenting, CTP showed completely restored blood flow to the pre-existing hypoperfused territories. The 30 day mRS score was stable or improved after stenting in 3/4 patients.